Hypokalemic nephropathy in the rat. Role of ammonia in chronic tubular injury. - Tolins, J P; Hostetter, M K; Hostetter, T H (The Journal of Clinical Investigation, 1987)
Chronic potassium deficiency results in progressive tubulointerstitial injury, associated with augmented renal ammoniagenesis. We investigated the role of elevated renal ammonia levels and the interaction of ammonia with the complement system in this injury. Potassium deficiency was induced in rats by feeding a low potassium diet. Experimental animals received 150 mM NaHCO3 or equimolar NaCl, as drinking water. After 3 wk, NaHCO3 supplemented rats demonstrated decreased ammonia production, less renal hypertrophy, less histologic evidence of injury, and less proteinuria. In in vitro studies on normal cortical tubular fragments, the addition of ammonia to serum in concentrations comparable to renal cortical levels in potassium-deficient animals significantly increased tubular deposition of C3 as quantitated by a radiolabeled antibody binding technique. Thus, alkali supplementation reduced chronic tubulointerstitial disease in a rat model of hypokalemic nephropathy. We propose that increased cortical ammonia levels contribute to hypokalemic nephropathy through ammonia-mediated activation of the alternative complement pathway. Images